Crises boursières, bulles spéculatives et raitionalité économique - Adam, Marie-Christine; Szafarz, Ariane (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
In October 1987 the stock markets across the world witnessed an unprecedent crash of which both economists and financial analysts are still trying to under-stand the origin. One of the most controversial interpretations of this event is the speculative bubble hypothesis according to which long overvalued stock prices readjusted to realistic values in october 87. This interpretation is particularly interesting given that new "bubble" theories have been developed within the framework of rational expectations models during the last ten years. This paper presents a critical analysis of these theories and evaluates their potential for our understanding of the stock market crash.